The Road Back to The Structure - Ortiz Ayuso, Jesús (Analysis. Journal of Philosophical Research, 2024)
In this text, we review the volume edited by K. Brad Wray: Kuhn's The Structure of Scientific Revolutions at 60. This book collects a series of essays in which various authors analyze The Structure of Scientific Revolutions (Thomas S. Kuhn's magnum opus) decades after its appearancei n the 1960s. In tune with the essence of the original work, our commentary returns to significant mid-twentieth-century issues related to the creation of The Structure, in particular the context in which it was developed and its impact on the philosophical and scientific landscape. However, as the authors of this volume argue, Kuhn's classic work raises matters that remain unresolved, questions that are deeply relevant to the contemporary scientific horizon and that will resonate in our brief analysis.